233k views
5 votes
Which shows 42^2 − 28^2 being evaluated using the difference of perfect squares method?

422 − 382 = (1,764 − 1,444)(1,764 + 1,444) = 1,283,200

422 − 382 = 1,764 − 1,444 = 400

422 − 382 = (42 − 38)2 = (4)2 = 16

422 − 382 = (42 + 38)(42 − 38) = (70)(4) = 280

2 Answers

3 votes

Answer:

None

Explanation:

The general form of the difference of perfect squares method is:
a^2-b^2=(a+b)(a-b)

Demonstration

The right part of the previous equation could be split like this:


a^2-b^2=a^2-a\cdot b + a\cdot b - b^2

Which can be simplified like this:


a^2-b^2=a^2-b^2

We have obtained the same result

Real problem

According to the problem
42^2 - 28^2 the development would be:


42^2 - 28^2=(42+28)\cdot (42-28)

The idea is to solve each pair of parenthesis and then to multiply.


42^2 - 28^2=(70)\cdot (14)=980

Thus, the result is not in the options because the problem asks for
42^2 - 28^2 and the options are related to
42^2 - 38^2

User Nachshon Schwartz
by
5.7k points
6 votes

Answer:


42^(2) -28^(2) =980

Explanation:

If you evaluate the equation using the factorization method by difference of perfect squares, it would be done as follows


a^(2) -b^(2)  = (a+b)(a-b)

Therefore


42^(2) -28^(2)   =   (42-28)(42+28)

Solving


(14)(70)=980

User Kevin Tan
by
6.8k points